2006
DOI: 10.1038/sj.cdd.4401863
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine induces Nrf2-mediated transcriptional activation of heme oxygenase-1 in protection of auditory cells from cisplatin

Abstract: We investigated the cytoprotective mechanisms of flunarizine in cisplatin-induced death of auditory cells. Concomitant with an increase in viability, treatment with flunarizine resulted in a marked dissociation of Nrf2/Keap1 and subsequent intranuclear translocation of Nrf2, which was mediated by PI3K-Akt signaling. Overexpression of Nrf2 protected cells from cisplatin along with transcriptional activation of ARE to generate heme oxygenase-1 (HO-1). Pretreatment with flunarizine predominantly increased the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 50 publications
(52 reference statements)
2
72
0
Order By: Relevance
“…CoPPIX inhibits cisplatin-induced death in the HEI-OC1 auditory-derived cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). HO-1 expression has been reported in cochlear hair cells and stria vascularis following a variety of stressors, including noise stress, heat stress, and pharmacological induction (Fairfield et al 2004;Lopez et al 2008;Kim et al 2009;Matsunobu et al 2009;Fetoni et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CoPPIX inhibits cisplatin-induced death in the HEI-OC1 auditory-derived cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). HO-1 expression has been reported in cochlear hair cells and stria vascularis following a variety of stressors, including noise stress, heat stress, and pharmacological induction (Fairfield et al 2004;Lopez et al 2008;Kim et al 2009;Matsunobu et al 2009;Fetoni et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological induction of HO-1 is protective against multiple stresses in many tissue types, including ischemia-reperfusion injury in liver and retina (Tsuchihashi et al 2007;Sun et al 2010). Several studies have demonstrated that inducers of HO-1 protect against cisplatin-induced death in the HEI-OC1 auditory cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). We have shown that HO-1 induction inhibits hearing loss and hair cell death caused by aminoglycoside antibiotics (Francis et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The NF-B reporter plasmid contains three copies of the B-binding sequence fused to the firefly luciferase gene (Clontech, Mountain View, CA). The ARE-luciferase reporter plasmid contains enhancer 2 (E2) and a minimal promoter sequence of the mouse HO-1 gene fused to the luciferase gene (So et al, 2006). BV2 cells (2 ϫ 10 5 cells per well in a 12-well plate) were transfected with 1 g of the reporter construct mixed with Geneporter.…”
Section: Methodsmentioning
confidence: 99%
“…For example, flunarizine inhibits membrane lysis and DNA fragmentation in explanted embryonic rat ventral mesencephalic cells [4] and impairs neuron death induced by a number of stimuli, including serum starvation and growth factor deprivation [5,6] and oxidative stress [7,8]. Flunarizine also protects auditory cells from the cytotoxic effects of cisplatin by inducing cytoprotective Akt activation and expression of heme oxygenase-1 [9]. Conversely, in some types of cancer cells flunarizine causes or potentiates cell death.…”
Section: Introductionmentioning
confidence: 99%